Ação farmacológica do 4,4’-dicloro-difenil disseleneto em modelos de hiperglicemia e obesidade em ratos - Quines, Caroline Brandão (2017)
The obesity epidemic is a worldwide public health problem and is considered one of the leading causes of death and disability worldwide. This is because the pathophysiology of this disease is extremely complex and involves a series of events in cascades that can even evolve into irreversible damage. Regarding treatment, drugs currently available for the treatment of obesity are often inefficient and have adverse effects, so the search for new drugs for the treatment of metabolic diseases has been growing so much in recent years. In this context, organic compounds of selenium have been studied in the last decades, mainly due to their diverse pharmacological activities, among them, antioxidant, neuroprotective, anticancer, antiviral, immunosuppressive, antimicrobial, anxiolytic, antidepressant-like and anti-inflammatory. However, these compounds have recently attracted attention because of their beneficial effects on the regulation of metabolic homeostasis. The present thesis aimed to investigate the pharmacological effects of 4,4'-dichloro-diphenyl diselenide, (p-ClPhSe)2 in hyperglycemia and obesity models induced by the administration of fructose or monosodium glutamate (MSG) in rats. In the manuscript 1, an insulin-mimetic effect of (p-ClPhSe)2 was demonstrated in vitro; this compound stimulated the glucose uptake into skeletal muscle and its acute antihyperglycemic effect in a model of hyperglycemia induced by the administration of fructose in rats. Furthermore, in the manuscript 1, acute treatment with (p-ClPhSe)2 protected against liver metabolic alterations induced by fructose; this compound redirected the carbohydrate metabolism. In that sense, in the article 1, a homeostatic effect of subchronic treatment with (p-ClPhSe)2 was demonstrated, this compound reduced the first signs of obesity induced with the administration of GMS in rats. Whereas in the manuscript 2, it was possible to observe a hepatoprotective effect of subchronic treatment with (p-ClPhSe)2 against the mitochondrial dysfunction, oxidative stress and inflammation induced by the administration of GMS in rats. In addition, a beneficial effect of subchronic treatment with (p-ClPhSe)2 against metabolic dysfunction in blood, liver and skeletal muscle induced by the administration of GMS in rats was demonstrated in manuscript 3. Taken together, the present results demonstrated that the compound, (p-ClPhSe)2, has several pharmacological properties, such as antihyperglycemic, insulin-mimetic, anti-inflammatory and antioxidant. It is known that drugs used for the treatment of obesity are often inefficient due to the complications present during the progression of obesity. Considering the pharmacological effects of (p-ClPhSe)2 demonstrated in the present study, this organic compound of selenium may be a future therapeutic alternative for the treatment of this pathology and its complications.